(untitled) (Contemporary Mathematics, 2024)
In this paper we advocate a new method to compute the eigenmodes of real symmetric positive definite matrices. Our method involves the zeros of a quartic polynomial, shifted inverse iteration and deflation of two eigenmodes simultaneously.